Determining Production Standard Time for Consumable Paper Products to Optimize Production Output Using Time Study Method - Anugrah, Siti Nabilah Putri; Alifin, Fakhri Ikhwanul (Fakultas Teknik Universitas Tulang Bawang, 2026)
One of the products of this consumable paper and packaging manufacturer is the ream-type consumable paper. The consumable paper production process still involves a lot of work from machine operators, so the company always designs and then implements changes as an effort to improve. These changes actually make operators need to adapt because work procedures are also undergoing changes, which will also affect production lead times and production output. Therefore, it is necessary to carry out a time study which can then be used as a basis for creating work standards for operators. The method used in this research is direct measurement of working time, namely the stopwatch time study approach. The research results show that the standard times for conditions 1 to condition 4 are respectively 4632,97 seconds, 4718,97 seconds, 4929,80 seconds and 5024,80 seconds. The amount of standard output that the company can obtain in 1 work shift for conditions 1 to condition 4 respectively is 163,5 packs/shift, 160,2 packs/shift, 153,4 packs/shift, and 150,5 packs/shift. Meanwhile, the work element that determines the lead time is work element D. Keywords: Output Optimization, Stopwatch Time Study, Work Standards